Factors affecting the sexual health of newly married couples: A qualitative study of experts\' point of views - Zabihollah Gharlipour; Leila GHazvinian; Zohreh Khalajinia; Farideh Khalajabadi Farahani; Mostafa GHazvinian (Payesh)
Objective(s): Sexual health is one of the main aspects of health that strengthens the foundation of the family. Therefore, a study was conducted aiming to explore the factors affecting the sexual health of newly married couples from the point of view of experts. Methods: This qualitative study was conducted by purposeful sampling in 2018 (May-Nov) with the participation of 20 experts using in-depth individual semi-structured interviews. All interviews were recorded and typed. The data was analyzed using conventional content analysis method and MAXQDA.10 software. Results: Factors affecting sexual health were explained in three categories and seven sub- categories. The three main categories included family factors (sexual education and economic-social status), individual factors (physical-mental health, interpersonal relationships) and marital factors (sexual schemas, sexual problems and sexual conversation). Conclusion: Based on the results obtained from the present study, couples need to receive sufficient information and special skills in psychological, individual and family, marital and socio-religious topics for improved sexual health.